Shadow banks and the collateral multiplier - Thomas R. Michl; Hyun Woong Park (University of Massachusetts, Department of Economics, 2021)
With an emphasis on contributing to macroeconomic pedagogy we examine the collateral multiplier by comparing it to the traditional money multiplier in a simplified framework of traditional banking and shadow banking in which government bonds are the core assets. While the money multiplier is a measure of the ability of the banking system to intermediate sovereign debt by creating deposits, the collateral multiplier is a measure of the shadow banking system's ability to inter- mediate sovereign debt by creating shadow money. It also measures the degree of re-use of sovereign debt as collateral. In this setup, the collateral multiplier is defined as the ratio between dealer banks' matched book repo activity relative to their trading book. Using the New York Fed's Primary Dealer Statistics data, we empirically estimate the collateral multiplier for U.S. Treasury repo collateral. Our model and empirical results shed light on the transmission mechanisms of monetary policy channeled through shadow banks and on the U.S. Treasuries market turmoil induced by COVID-19 in March 2020.
Keywords: A2; E51; 330; shadow banks; collateral multiplier; rehypothecation; Treasury bond; repo